Fukushima fallout at Milano, Italy - Ioannidou, Alexandra; Manenti, Simone; Luigi Gini; Groppi, Flavia (Journal of environmental radioactivity, 2012)
The radionuclides 131I, 137Cs and 134Cs were observed in the Milano region (45°) of Italy early after the nuclear accident in Fukushima, Japan. Increased atmospheric radioactivity was observed on an air filter taken on 30 March 2011, while the maximum activity of 467 μBq m−3 for 131I was recorded at April 3–4, 2011. The first evidence of Fukushima fallout was confirmed with 131I and 137Cs measured in precipitation at two sampling sites at Milano on 28 March, 2011, with the concentrations of 131I and 137Cs in the rainwater equal to 0.89 Bq L−1 and 0.12 Bq L−1, respectively. A sample of dry deposition that was collected 9 days after the first rainfall event of 27–28 March, 2011 showed that the dry deposition was more effective in the case of 137Cs than it was for 131I, probably because iodine was mainly in gaseous form whereas caesium was rapidly bound to aerosols and thus highly subject to dry deposition. The relatively high observed values of 137Cs in grass, soil and fresh goat and cow milk samples were probably from Chernobyl fallout and global fallout from past nuclear tests rather than from the Fukushima accident. Finally, a dose assessment for the region of investigation showed clearly that the detected activities in all environmental samples were very far below levels of concern. ► Radioactive plume from Fukushima reactor accident reached Milano, Italy. ► 131I, 137Cs and 134Cs were determined in rainwater, air, soil, grass and milk samples. ► The 134Cs/137Cs activity ratio values in air was about 1. ► High observed values of 137Cs in grass, soil and milk samples are not due to Fukushima accident. ► The dose assessment show that the observed activities are very far below levels of concern.